A Historical-Philological Reassessment of Al-Arba'ūna fi Al-Tasawwuf and Its Contribution to Early Sufi Engagements with Hadith - Muhammad Royyan Faqih Azhary; Ahmad Firdaus; M. Hazim; Achmad Roziqi; Advan Navis Zubaidi (Universitas Nurul Jadid, 2025)
This study analyzes the epistemological intersection between Sufism and Hadith Science through an in-depth examination of the work of Abū ‘Abd al-Raḥmān al-Sulamī, al-Arbaʿūn fī al-Taṣawwuf. Using a historical-philological method, the research reveals the mechanism of the